Reflections on the physical education formation and its application for working with handicapped pupils - Filus, Josiane Fujisawa; Martins Junior, Joaquim (Journal of Physical Education (Maringá), 2008)
The number of handicapped people who practice physical activities has been increasing in the last years. Due to their eclectic formation, the professionals of the area, besides taking care of this population in gymnasiums, also teach in schools, which, due to school inclusion, include the handicapped pupils in their regular classes. In addition, it searched the identification of places where the professionals work the activities developed by them and also their opinion on the inclusion of pupils with deficiency into regular school. In this context, this study aimed at identifying if the education offered by the Physical Education course gives subsides for the professional concerning the work with this special population. Some interviews applied to a sample of fourteen professionals who work in this field verified that half the sample had not had contents related to handicapped people during their undergraduate course, and that the difficulties in the beginning of their work were connected to the absence of experience and knowledge. It was also observed that several of them are not satisfied with the education they had, and that they miss both greater knowledge on people with deficiency and preparation on how to deal with them, problems that are only overcome with practice and experience. It was concluded, therefore, that all the subjects concerning the Physical Education undergraduate course should offer contents in the sense of enabling an educator to attend the educational needs of these pupils.